(untitled) (Revista BOEM, 2024)
The aim of this article is to present an experience report on the production of digital videos for teaching geometry with the support of the grid in the early years of elementary school. An intervention was carried out in a public school in Maceió, in the fifth year of the early years of elementary school. The videos were produced by the teacher and made available in the virtual environment as a digital learning resource for the classes involved. The videos deal with the teaching of geometry, with the object of knowledge being the enlargement and reduction of polygonal figures on checkered meshes: recognizing the congruence of angles and the proportionality of the corresponding sides. And as a skill (EF05MA18) "recognizing the congruence of angles and the proportionality between the corresponding sides of polygonal figuresin situations of enlargement and reduction on checkered grids and using digital technologies". With this, we point out that the videos provide learning that involves creativity and the possibility of re-signifying geometry concepts, which emerge from themes and environments in the student’s daily life, promoting greater involvement and engagement in math classes.